THE INFLUENCE OF PRODUCT QUALITY AND SERVICE QUALITY ON CUSTOMER SATISFACTION AT MARSALIA EMBROIDERY IN MALANG CITY - Naila Ruhama; Musthofa Hadi; Tri Yulistyawati Evelina (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2024)
In this contemporary period, commerce plays a crucial role in the advancement of the economy and society. The fashion industry is currently experiencing significant growth in Indonesia. Situated in Malang City, Marsalia Embroidery is a thriving fashion enterprise. The primary objective of this research is to assess how customer satisfaction at Marsalia Embroidery is impacted by the quality of their products and services. By conducting a survey, involving 86 negligee purchasers, this quantitative study followed a purposive sampling approach. Subsequently, the obtained data will undergo analysis through multiple linear regression and hypothesis testing. The findings of this investigation reveal that both product quality and service quality individually influence customer satisfaction to a certain degree. Collectively, these two variables hold a substantial sway over customer satisfaction, accounting for 74.1%, while the remaining 25.9% is attributed to other unexplored factors. Therefore, it can be deduced that both product quality and service quality have a partial and collective impact on customer contentment. Marsalia Embroidery is expected to increase the consistency of its products by maximizing the quality check process, so that consumers will receive products that are free from defects and have good standards. In addition, Marsalia Embroidery should also evaluate the reliability of employees in serving consumers, in order to meet the services expected by consumers.